Influence of annealing temperature on corrosion resistance of tio2 nanotubes grown on ti–30ta alloy - Capellato, Patricia; Sachs, Daniela; Vilela, Filipe Bueno; Melo, Miriam M.; Silva, Gilbert; Rodrigues, Geovani; de C. Zavaglia, Cecilia A.; Nakazato, Roberto Z. [UNESP]; Claro, Ana Paula R. A. [UNESP] (MDPI, 2020)
With little success, researchers has been searching for alloys with elements such as tantalum to improve the long-term life of implants. The Ti–30Ta alloy presents an elastic modulus E = 69 GPa that is close to that of bone (E = 17–25 GPa) than Ti cp (E = 105 GPa). In addition, nanostructure surface modification influences cell behavior and antimicrobial activity. So, this study investigates the corrosion behavior of surface modification by TiO2 nanotube grown on Ti–30Ta alloy after anodization process in the electrolyte glycerol + NH4F 0.25% at 30 V, for nine hours without annealing and annealed in 450◦C, 530◦C and 600◦C (5◦C/min). The electrochemical behavior was evaluated by three electrodes cell. The counter-electrode of graphite, reference-electrode of saturated calomel electrode and working-electrode at electrolyte of 0.15 M NaCl + 0.03 M NaF, with pH = 6 for 8000 s. The scanned region ranged from −0.8 V to values up to 3.5 V with a sweep rate 0.166 mV/s. Potentiodynamic polarization curves were obtained with a potentiostat. The sample was characterized by scanning electron microscopy (SEM) imaging, X-ray diffraction analysis (XRD) and wettability with a contact angle goniometer. We concludes from the obtained results that all treatment surfaces are hydrophilic (<90◦). The surface covered with TiO2 nanotube crystallinity showed anatase phase after annealing at 450◦C, 530◦C and 600◦C; the exceptions were the anodized-without-annealing treatment and without-surface-modification alloys. The electrochemical behavior of the five groups investigated showed similar high resistance to corrosion solution under all conditions.
Keywords: Annealing temperature; Corrosion resistance; TiO2 nanotube; Ti–30Ta alloy